2011
DOI: 10.1007/s00421-011-1857-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-dive ultrasound detection of gas in the liver of rats and scuba divers

Abstract: In a previous study, we obtained histologic documentation of liver gas embolism in the rat model of rapid decompression. The aim of the study was to assess in the same model occurrence and time course of liver embolism using 2-D ultrasound imaging, and to explore by this means putative liver gas embolism in recreational scuba divers. Following 42 min compression at 7 ATA breathing air and 12 min decompression, eight surviving female rats were anesthetized and the liver imaged by ultrasound at 20 min intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…This observation poses the problem of the integrity of digestive function in the context of DCS. As it happens, liver disorders have already been mentioned in DCS in humans 27,28 and animals 19,29,30 .…”
Section: Expression Of Metabolites Indicating An Alteration Of the Homentioning
confidence: 93%
“…This observation poses the problem of the integrity of digestive function in the context of DCS. As it happens, liver disorders have already been mentioned in DCS in humans 27,28 and animals 19,29,30 .…”
Section: Expression Of Metabolites Indicating An Alteration Of the Homentioning
confidence: 93%
“…VGE detection has been applied to various animal models including rats and mice [4]. The presence of VGE can be described using one of several grading scales that have been previously developed (Kisman-Masurel or Spencer for Doppler, Eftedal-Brubakk for echocardiography) [7][8][9].…”
Section: Plos Onementioning
confidence: 99%
“…Previous work has shown that higher VGE grades correlate with an increased risk of DCS, and a VGE grade of zero corresponds with low risk for DCS [10,11]. However, these VGE grades cannot be directly used as a surrogate endpoint for DCS outcome in dive trial studies aiming to test new decompression procedures [4]. Previous publications have used these scales to assess the risk associated with a certain dive profile, describe the impact of a certain treatment, and aid in tracking the onset of DCS in rats or mice [12][13][14].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation